The Development of an Android-Based Classical Guidance and Counseling Service Application for Junior High Schools - Rappetang Rappetang; Suciani Latif (Program Studi bimbingan Konseling PPs UNM Makassar, 2022)
This study aims to (1) describe the needs for the development of an Android-based classical guidance and counseling service mobile application in 5 schools in Pujananting District, (2) describe the prototype of an Android-based classical guidance and counseling service mobile application, and (3. determine the level of validity of an Android-based classical guidance and counseling service mobile application. The validity testing was conducted by a content expert and a technology expert to ensure the utility, accuracy and feasibility of the application. The study was conducted by adapting to the stages of Research and Development by Borg and Gall. Data were collected using observations, interviews, and questionnaires, and were analyzed using qualitative and quantitative data analysis. The results showed that (1) the Android-based classical guidance and counseling service application needed to be developed in 5 junior high schools in Pujananting District to facilitate students in receiving online counseling services, (2) the prototype of application through planning and developing early product as well as validity testing was found to have high levels of utility and feasibility, (3) the Android-based classical guidance and counseling and service application was useful, feasible and accurate as a media to provide online classical guidance and counseling guidance services.